Il pulpito e il pavimento di San Liberatore alla Maiella: distruzione, alterazione e ricomposizione degli arredi liturgici (Fenestella. Inside Medieval Art, 2020)
The Pulpit and the Floor of San Liberatore alla MaiellaThis paper has been inspired by the study of the Abruzzi liturgical furnishings and, in particular, by a fundamental work of Otto Lehmann-Brockhaus presented in 1944: Die Kanzeln der Abruzzen im 12. und 13. Jahrhundert.Our aim is to focus on the abbey church of San Liberatore alla Maiella, the once powerful and widely known Benedictine order, pivot of political control of Montecassino in Abruzzo. Its founding is unknown, but dates back to a time before the year 990, when the abbey was destroyed by an earthquake.We will pay particular attention to the reconstruction of the architectural development of the church – transformed into a cemetery from the municipality of Serramonacesca in the 19th century – and its medieval pulpit and floor, in particular on their conservation history and their decoration.Our focus, here, is to argue – on the basis of a full analysis of the available sources on the history and restorations of the abbey – that the pulpit is the result of an assemblage carried out between the years 1970 and 1971, and that the floor was made in two distinct interventions, carried out between the 11th and 13th centuries.
Keywords: Abruzzo; Benedettini; Arredi liturgici; Spazio liturgico; Pulpito; Ambone; Opus sectile; Medioevo; Montecassino